Comparison of field emission performances and durability of three nanocarbon materials. (July 2020) - Youh, Meng-Jey; Lin, Chun-Shuan; Pu, Nen-Wen; Liu, Yih-Ming; Youh, Ru-Yi; Li, Hao-Qian; Tang, Pei-Yu; Lin, Ming-Hsien; Ger, Ming-Der
Abstract: The performances and operation lifetime of field emission (FE) cathodes made by spray-coating three different nanocarbon materials—carbon nanotubes (CNTs), graphene (GE), and carbon nanocoils (CNCs)—were compared. Though CNTs had the benefits of the lowest turn-on field, CNCs exhibited the most stable cycle-to-cycle repeatability and a significantly longer life than CNTs and GE under a continuous high-current-density operation. The microscopic morphology and Raman spectra of these nanocarbon emitters before and after the 50-h life tests were examined in order to understand the damage mechanism and the cause of their distinct performance decay behaviors. The results indicated that CNCs, whose diameters are significantly larger than those of CNTs and the thickness of GE, can withstand the thermal effects of high current density with the least degree of damage in the morphology and microstructure. According to our performance and life tests, CNTs are most suitable for low-voltage small-current FE applications because of their highest field enhancement factor and lowest turn-on field, while CNCs are a more favorable candidate for high-voltage long-term applications such as FE x-ray tubes. Highlights: The performances of FE cathodes spray-coated with CNTs, GE, or CNCs are compared. Comparing the FE characteristics and the lifetime under high current operation. The current decay behaviors over long-term operation are studied in detail. The three carbon materials exhibited very different damage behaviors. CNCs are the best candidate for high-voltage long-term applications.